Changes in adiposity modulate the APOA5 genetic effect on blood lipids: A longitudinal cohort study. (June 2022) - Lin, Hong; Xuan, Liping; Xiang, Jiali; Hou, Yanan; Dai, Huajie; Wang, Tiange; Zhao, Zhiyun; Wang, Shuangyuan; Lu, Jieli; Xu, Yu; Chen, Yuhong; Wang, Weiqing; et al.
Abstract: Background and aims: The Apolipoprotein A5 (APOA5) rs662799 was significantly associated with blood lipid level at genome-wide significance level. Whether dynamic changes of adiposity influence the effect of lipid loci on long-term blood lipid profile remains unclear. We assessed interactions of 5-year body mass index (BMI) change and rs662799 genotypes with risk of incident dyslipidemia and longitudinal changes in serum lipids in a prospective cohort. Methods: We included 4329 non-dyslipidemia participants aged ≥ 40 years at baseline from a well-defined community-based cohort and followed up for an average of 5 years. BMI and blood lipids were measured at baseline and follow-up. Results: The association of each rs662799 A-allele with risk of incident dyslipidemia was stronger along with the increase in BMI change level, with the odds ratios (OR) increasing from 1.03 in the lowest tertile of BMI change (< 0.02 kg/m 2 ) to 1.17 in the second (0.02–1.29), and 1.46 in the highest tertile (> 1.29) ( p for interaction < 0.001). Associations of each 1-unit of BMI (kg/m 2 ) increase with incident dyslipidemia were more prominent in the AA carriers (OR = 1.50, 95%CI [1.26–1.80], p  < 0.001), while much weaker in the GA (OR = 1.10) or GG carriers (OR = 1.09) ( p for interaction  = 0.002). Similar results were found for the risk of incident higher triglycerides (TG) and lower high-density lipoprotein cholesterol (HDL-c), or the longitudinal changes in log10 -TG (all p for interaction ≤ 0.02). Conclusions: BMI changes significantly modulate rs662799 genetic contribution to dyslipidemia and long-term lipid profile, which provide new evidence for personalized clinical management of lipids according to individual genetic background. Graphical abstract: Image 1 Highlights: APOA5 rs662799 was associated with incident dyslipidemia, higher TG and lower HDL-c. Associations of APOA5 rs662799 with risk of incident dyslipidemia, longitudinal changes in TG and HDL-c levels were stronger in the higher BMI increase groups. Associations of BMI increase with incident dyslipidemia, increase in TG or decrease in HDL-c were more prominent in APOA5 rs662799 AA carriers. BMI changes significantly modulate the APOA5 rs662799 genetic contribution to long-term lipid profiles.